A Rapid Method for Low Temperature Microencapsulation of Phase Change Materials (PCMs) Using a Coiled Tube Ultraviolet Reactor - Jawaad A. Ansari (17542257) (2021)
Microencapsulation of phase change materials (PCMs) remain a suitable option within building materials, as they contribute to the thermal mass and provide an energy buffer, an added benefit. This paper presents a novel method for the rapid fabrication of microencapsulated phase change materials (PCMs) at ambient conditions in a perfluoroalkoxy (PFA) coiled tube ultraviolet (UV) reactor. The objective of this study was to optimize key parameters such as the product yield and quality of the as-prepared microcapsules. Rubitherm® RT-21™ PCM was microencapsulated within shells of poly-methyl-methacrylate (PMMA) through a suspension emulsion polymerization approach, where the crosslinking of polymers was driven by UV radiations with an appropriate photoinitiator. The characteristics of the resulting PCM microcapsules were found to be affected by the volumetric flow rate of the emulsion inside the coiled tube reactor. Higher volumetric flow rates led to higher PCM contents and higher microencapsulation efficiency, resulting in an average particle size of 6.5 µm. Furthermore, the effect of curing time on the PCM microcapsule properties was investigated. The optimum encapsulation yield, conversion, efficiency and PCM content were observed after 10 min of polymerization time. The thermal analysis indicated that the developed process had an efficiency of 85.8%, and the capsules were characterized with excellent thermal properties. Compared to the conventional thermal microencapsulation processes, the use of a coiled tube UV reactor with an appropriate photoinitiator enables the encapsulation of heat-sensitive PCMs at ambient conditions, and reduces the microencapsulation time dramatically. As a result, this novel microencapsulation approach can lead to a wider scope of PCM encapsulation and enable rapid, continuous and potentially large-scale industrial production of PCM microcapsules with low energy consumption. Other Information Published in: Energies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/en14237867 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.